Reinforced Subbases and Application of Other Chosen Parameters in Sleeper Subgrade Dimensioning - Izvolt, Libor; Kardos, Jan; Mecar, Martin (Communications - Scientific letters of the University of Zilina, 2007)
The paper focuses on reinforced subbases which are frequently applied to modernised railway tracks of Slovak Railways (ZSR) despite certain theoretical and normative deficiencies. Based on the evaluation of laboratory measurements other parameters which are to be taken into consideration when dimensioning a sleeper subgrade construction are specified.